Developing Wordwall-Based Educational Games to Improve Number Symbol Recognition Skills in Children Aged 5–6 Years - Baiq Amlin Apriliani; Gunawan Gunawan; Baik Nilawati Astini (Indonesian Journal of Elementary and Childhood Education, 2026)
The use of technology-based learning media in early childhood education has not been optimally implemented, particularly in improving the ability to recognize number symbols among children aged 5–6 years. Therefore, it is necessary to develop interactive learning media that are appropriate to the characteristics of early childhood learners. This study aimed to develop and evaluate the feasibility and effectiveness of an educational game using Wordwall to improve children aged 5–6 years' ability to recognize number symbols. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The study was conducted at a kindergarten in East Lombok Regency, with Group B children as the research subjects. Data collection techniques included observation, validation questionnaires from media and material experts, and pretest and posttest assessments.  The validation results indicated that the Wordwall educational game was categorized as highly feasible for use in learning activities.  The effectiveness test results showed an increase in the average children’s cognitive ability from a pretest score of 69.41 to a posttest score of 98.24, with an N-Gain value of 0.97, which falls into the high category.  Therefore, it can be concluded that the Wordwall educational game is feasible and effective in improving the ability to recognize number symbols in children aged 5–6 years.